THE EFFECT OF CARTOON MOVIE ON STUDENTS’ LISTENING COMPREHENSION AT ELEVENTH GRADE OF SMA NEGERI 2 BANGKINANG KOTA - Nur, Nadia (Journal of English Language and Education, 2024)
This study aims to determine whether using the cartoon movie affects students’ listening comprehension in eleventh grade for the academic year 2022/2023. The research was conducted on eleventh grade MIA students at SMAN 2 Bangkinang Kota. The study involved 63 students who were divided into 2 classes, namely class XI MIA 1 as the control class which consists of 30 students, and XI MIA 5 as the experimental class with 27 students present that day. The experimental class uses the cartoon movie as media learning and the control class is taught using conventional media which is using the audio speaker. The data were analyzed using the SPSS 25 program. Based on the results obtained, the average value of students in the experimental class was 61.85 and 48.33 in the control class. The data obtained showed a significance (2-tailed) 0.001 0.05. This means that H0 is rejected and Ha is accepted. This indicates that there are differences in students’ listening comprehension between students who are taught using the cartoon movie and students who are taught using audio speakers. Based on the findings, it can be concluded that cartoon movie effectively affects students’ listening comprehension.Keywords: Listening Comprehension, Cartoon Movie